THE COMFORT OF DIGITAL TYPING WITH A USER EXPERIENCE (UE) APPROACH - Suhartana, I Ketut Gede; Wibawa, I Gede Arta; Pramartha, Cokorda; Giri, Gst Ayu Vida Mastrika; Satyaninggrat, Luh Made Wisnu; Setiawan, Gde Iwan (Proceeding International Conference on Information Technology, Multimedia, Architecture, Design, and E-Business, 2024)
Computers as one of the human aids are used to ease human life. Some of the advantages of using computers are that they can be used to play music, watch videos and create documents. In making general documents, users use an input device called a keyboard. The type of keyboard that is widely used is the "QWERTY" keyboard. The characteristic of this keyboard is that it is arranged starting with the arrangement of the letters Q, W, E, R, T, Y and so on as the name suggests. Typing a manuscript using Balinese characters will be difficult if using this type of QWERTY keyboard. This happens because this keyboard only consists of Latin letters. This study developed a special keyboard with Balinese characters (Ergonomics-Based Smart Keyboard) to be used for typing digital lontar manuscripts. The arrangement of this keyboard consists of Balinese only. Another problem is the different levels of constancy of users so that it will affect the typing results. Therefore, this study was conducted to determine the correlation of constancy to the comfort of typing digital lontar with the Ergonomics-Based Smart Keyboard. This study uses descriptive correlation techniques. The research sample was 20 subjects selected randomly with inclusion and exclusion criteria. The test results on the correlation of the two variables of constancy with comfort showed a strong relationship with a value of rxy = 0.59 with a confidence level of p = 0.006. In other words, both variables have a significant relationship between decreasing constancy with decreasing comfort or increasing constancy with increasing comfort with a value of p <0.05 in typing digital palm leaves using a smart keyboard.